2018
DOI: 10.1186/s40694-018-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plant cell wall degradation by light in Trichoderma

Abstract: Trichoderma reesei (syn. Hypocrea jecorina) is the model organism for industrial production of plant cell wall degradating enzymes. The integration of light and nutrient signals for adaptation of enzyme production in T. reesei emerged as an important regulatory mechanism to be tackled for strain improvement. Gene regulation specific for cellulase inducing conditions is different in light and darkness with substantial regulation by photoreceptors. Genes regulated by light are clustered in the genome, with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 122 publications
3
63
0
Order By: Relevance
“…Even though Neurospora was grown under constant light conditions for the present study, the data reveal abundant phosphorylations present in clock components. Crosstalk between gene regulation in response to different nutritional conditions and the light response pathway is extensive (Schmoll, 2018; Stappler et al, 2017) and was also shown in N. crassa (Sancar et al, 2012; Schmoll et al, 2012). FREQUENCY (FRQ; NCU02265) is a key component of the Neurospora circadian clock, allowing precise daily control of several processes, including metabolism (Hurley et al, 2016; Montenegro-Montero et al, 2015).…”
Section: Resultsmentioning
confidence: 89%
“…Even though Neurospora was grown under constant light conditions for the present study, the data reveal abundant phosphorylations present in clock components. Crosstalk between gene regulation in response to different nutritional conditions and the light response pathway is extensive (Schmoll, 2018; Stappler et al, 2017) and was also shown in N. crassa (Sancar et al, 2012; Schmoll et al, 2012). FREQUENCY (FRQ; NCU02265) is a key component of the Neurospora circadian clock, allowing precise daily control of several processes, including metabolism (Hurley et al, 2016; Montenegro-Montero et al, 2015).…”
Section: Resultsmentioning
confidence: 89%
“…The LaeA/VeA/VeB complex genes, which were previously reported to be involved in ChA biosynthesis and cellulase production [ 40 ], were down-regulated in pG14 as well (log 2 Ratio = − 1.7, − 0.5, − 1.7). In addition, the photoreceptor env1 gene, connecting the light signaling and the cellulase gene transcript levels [ 41 ], was upregulated in pG14 in light (log 2 Ratio = 1.5) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the response to different substrates, cellulase gene transcript levels are also modulated by environmental factors especially light and by ENVOY (ENV1), the central component of the light signaling machinery in T. reesei [ 41 ]. The photoreceptor ENV1 mainly established connections with the heterotrimeric G-protein pathway and triggers posttranscriptional regulation of cellulase expression with light response.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in the optimal nutritional conditions, the growth-related metabolism should be approximately equal in the light and in the dark, but alterations in these conditions would affect the metabolic processes differently depending on the lighting status (Carlile, 1965). It has been proved that light regulates gene expression in Trichoderma reesei and the genes encoding CAZYmes are clustered together in the genome (Schmoll, 2018a). Therefore, it is hard to compare different fungal organisms growing in different media in the same lighting conditions.…”
Section: Discussionmentioning
confidence: 99%